THE PROBLEM OF PERCEPTION OF NON-CATEGORIC STATEMENTS IN ENGLISH AND RUSSIAN LITERARY TEXTS (Web of Teachers: Inderscience Research, 2024)
The given article is dedicated to the problem of perception of non-categoric statements in English and Russian literary texts. The study of depicted human emotions in a literary text is due to the fact that it is in it that one can expect the most complete functional manifestation of the pragmatic potential of emotional statements.